Copper in cancer: from limiting nutrient to therapeutic target - Tang, Xiaolong; Yan, Zaihua; Miao, Yandong; Ha, Wuhua; Li, Zheng; Yang, Lixia; Mi, Denghai (Frontiers in Oncology, 2023)
As an essential nutrient, copper's redox properties are both beneficial and toxic to cells. Therefore, leveraging the characteristics of copper-dependent diseases or using copper toxicity to treat coppersensitive diseases may offer new strategies for specific disease treatments. In particular, copper concentration is typically higher in cancer cells, making copper a critical limiting nutrient for cancer cell growth and proliferation. Hence, intervening in copper metabolism specific to cancer cells may become a potential tumor treatment strategy, directly impacting tumor growth and metastasis. In this review, we discuss the metabolism of copper in the body and summarize research progress on the role of copper in promoting tumor cell growth or inducing programmed cell death in tumor cells. Additionally, we elucidate the role of copper-related drugs in cancer treatment, intending to provide new perspectives for cancer treatment.